'The Options were Shrinking. Choices were Being Removed': Selected Literary Representations of the Consequence of Climate Change. Issue 1 (2nd January 2023) - Murray, Jessica
Abstract : This article considers the ways in which selected contemporary novels represent the limitation of options as a primary consequence of climate change. I will offer an ecocritical literary analysis of the following four novels by female authors: The New Wilderness (2020) by Diane Cook, A Children's Bible (2020) by Lydia Millet, Weather (2020) by Jenny Offill and The Last Migration (2021) by Charlotte McConaghy. The novels present worlds where very definite choices, in already severely constrained contexts, need to be made. These choices are matters of survival and they have nothing to do with fulfilling constructed consumer dreams. The texts offer worlds in which characters navigate radically new terrains where survival is an urgent imperative. I will consider how the notions of limitation and shrinking (of their worlds and their options) recur as leitmotifs throughout the novels and I will explore how this shrinkage forces them to reconsider not only their own actions but also the consequences of the actions of people in general, with a specific focus on the causal relationship between those actions and climate change.